Cartel Attributes and Cartel Performance: The Impact of Trade Associations. (13th December 2017) - Schuldt, Robert F.; Taylor, Jason E.
Abstract : This paper employs a cartel policy experiment, the National Industrial Recovery Act of 1933, to examine whether industries that have trade associations in place prior to cartelization were better able to attain collusive outcomes than otherwise. Trade associations could potentially help industries better formulate effective cartel rules and could help with monitoring. We find that industries with trade associations were more successful in achieving collusion–proxied by either reductions in industry output or increases in industry prices–than those without. In fact, industries without trade associations were generally unable to successfully collude under the NIRA.